Distribution of Stingless Bee (Trigona spp.) from Meliponiculture in South Sumatra Province, Indonesia - Rahmad, Beni; Damiri, Nurhayati; Hanafiah, Zazili; Adriani, Dessy (Jurnal Manajemen Hutan Tropika, 2024)
This study aims to determine species distribution by observing the stingless bees cultivated by the community in South Sumatra Province using meliponiculture. By visiting boxes and studying the entrance and characteristics of stingless bee hives at each research location, bee samples were obtained in six districts or cities where beekeepers exist. The study was conducted from January 2023 to May 2023. The type of bee species was identified in each culture box, the diameter of the entrance was measured, and the diameters of the honey pot and brood cell pot were measured. A descriptive analysis was performed to gain an overview of each entrance and nest. Based on the identification results, eight different varieties of stingless bees were discovered. Each research site had an unequal distribution of the eight varieties of bees. Lepidotrigona terminata, Heterotrigona itama, Lophotrigona canifrons, Geniotrigona thoracica, Tetrigona apicalis, Tetragonula testaceitarsis, Tetragonula fuscobalateata, and Tetragonula laeviceps are examples of stingless bees. Variations in the size of identified stingless bees affect the size of the hive, brood cell, honey pot, and entrance. The nest, brood cells, honey pot, and entrance grow in proportion to the size of the stingless bee. Differences in the form and size of the entrance can also distinguish between species.